Catalisadores de Au/ZrO2 e Au/In2O3/ZrO2: Efeito das propriedades eletrônicas e estruturais na atividade para desidrogenação do etanol e hidrogenação de CO2 - Augusto, Thiago de Melo (2022)
Au/ZrO2 and Au/In2O3/ZrO2 catalysts were developed for CO2 hydrogenation reaction and Au/ZrO2 for ethanol dehydrogenation. The monometallic gold catalysts supported on ZrO2 with different contents (0.3 to 5.0%w/w) were prepared by deposition-precipitation (DP) and analyzed by HRSTEM, DRIFTS-CO and in situ XPS as well as other characterization techniques. HRSTEM analysis proved the high dispersion of Au nanoparticles (NPs) with an average size around 15 Å. The ulltraestructural analysis also verified the presence of particles smaller than 20 Å (metal clusters) and isolated atoms with 2D and 3D configurations. The activity verified by ethanol dehydrogenation tests was higher for catalysts with Au content <1%. In situ XPS analyses indicated that a high dispersion of Au NPs, associated with heat treatment conditions at low temperature (200°C), promoted an increase in BE Au 4f7/2 binding energy, accompanied by surface defects and characterized by CO adsorption.The DFT results using clusters (3 and 13 Au atoms), indicated that the activation of ethanol on the surface of the clusters is not favorable, it must occur at the Au/ZrO2 interface and the determining step occurs on the surface of the clusters. The presence of low coordination sites formed by surface defects through the decrease of the Au charge and low heat treatment temperature suggest that they are of the 2D surface type, providing high catalytic activity and low activation energy (Ea) for the reaction. The increase of temperature in He treatment of the samples (from 200 to 600°C) increases the coordination number (NAu-Au) and the bond distance (RAu-Au), promoting a decrease of the catalytic activity. The adsorption of CO in linear form to the bridge type is favored with increasing Au loading and heat treatment temperature in He. This behavior is accompanied by the increase of NAu-Au and RAu-Au. Removal of defects on the surface by thermal activation leads to a decrease in electronic density and catalytic activity. Au/ZrO2, In2O3, In2O3/ZrO2, Au/In2O3, and Au/In2O3/ZrO2 catalysts were also evaluated for the CO2 hydrogenation reaction at high pressure (50bar). HRSTEM indicated a high dispersion of the Au on the support (In2O3/ZrO2) and of the In2O3 nanoparticles on the ZrO2. XPS spectra confirmed the interaction between In and Zr by deviations in the binding energy for the 3d 5/2 level of In and Zr and by differences between the reduction profiles by TPR-H2 for the bulk (In2O3) and the In2O3/ZrO2.Ex situ and in situ Raman, and XPS allowed confirming the increase in vacancies for this system with variation in the relative intensities of the decayed spectra. The yield to the methanol product was significantly higher for the Au/In2O3/ZrO2 system compared to the others (Au/ZrO2, In2O3, In2O3/ZrO2, and Au/In2O3), indicating that clusters and/or NPs of Au, as well as highly dispersed In2O3 NPs on ZrO2 favor the formation of oxygen vacancies in the active sites, increasing the CO2 adsorption strength, stabilization of reaction intermediates, and decreasing the reverse reaction of CO production with ~70% selectivity to methanol.